Peningkatan Hasil Belajar Siswa pada Pembelajaran Agama Katolik Melalui Metode Problem Based Learning Kelas IX SMP Negeri 2 Tujuh Belas Tahun 2024 - Servasius Kekok (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve student learning outcomes in Catholic Religion learning through the application of the Problem Based Learning Method in Class IX students of SMP Negeri 2 Seventeen in 2024. The approach taken in this research is quantitative with Classroom Action Research (PTK) consisting of Planning, Carrying out learning, observations, group discussions, individual assignments/tests, group awards and determining individual and group grades. Research Subject: Class IX students of SMP Negeri 2 Seventeen. Data collection techniques Direct Observation Techniques, Indirect Observation Techniques, Direct Communication Techniques, Indirect Communication Techniques, Measurement/Test Techniques, Documentation Techniques which are expected to be able to show changes in the actions given. The data obtained was analyzed using descriptive statistics. This research consists of three cycles. In the first cycle the average student score was 6.79 or 68.42%, and the student score in the second cycle was 8.83 or 75.17%. Meanwhile, the average value in the third cycle was 9.05 or 93.75%. From the results of this research, it can be concluded that learning using the Problem Based Learning Method for Class IX students at SMP Negeri 2 Seventeen is able to improve the remaining learning outcomes so that they meet the Minimum Completeness Criteria (KKM).